Calculations of chemical equilibrium with symbolic computation - Hidalgo, Ricardo (2014)
We show how a processor for symbolic computation can readily enable extensive calculations to describe the equilibria involving gases, the pH of an aqueous solution in the titration of a polyprotic acid, and complex ions as a function of concentration of ligand in aqueous solution.